Organic matter composition and inorganic nitrogen response to Hurricane Harvey’s negative storm surge in Corpus Christi Bay, Texas - Douglas, Audrey R.; Murgulet, Dorina; Greige, Megan; Das, Kousik; Felix, J. David; Abdulla, Hussain A. (Frontiers in Marine Science, 2022)
Extreme weather events, such as tropical storms and hurricanes, are known to deliver large amounts of freshwater (surface runoff) and associated inorganic and organic nutrients to estuaries and the coastal ocean, affecting water quality and nutrient budgets. However, while Hurricane Harvey produced an unprecedented 1000-year flood event in 2017 that inundated areas north of the landfall, like the Houston/Galveston region (TX, United States), the impact to the Corpus Christi area, south of the landfall, was an intermittent negative surge (∼0.5 m below mean sea level-msl), caused by the southerly direction of winds, and limited freshwater inflows. Using pre- and post- landfall surface-, pore- and groundwater nutrient measurements and dissolved organic matter (DOM) molecular characterization analyses, this study assessed the influence of negative storm surge on groundwater-surface water interactions and nutrient composition. Within 2 weeks following the first landfall, the forms and inputs of inorganic and organic nutrients fluctuated significantly nearshore Corpus Christi Bay. Sudden drops in sea level were correlated with pulses of NH4+ and disproportionately more DOC than DON, likely from a carbon-rich groundwater or benthic source with slightly lower labile characteristics. Recovery to msl drove higher proportions of nitrogenous DOM and lower dissolved inorganic nitrogen (DIN) inputs. An increased presence of sulfurized DOM derived from anaerobic microbial processing of organic matter mineralization in marine sediments post-landfall was facilitated by enhanced groundwater inputs and flushing of porewater due to considerable drops in sea level and steepening hydraulic gradients towards the coast. The induced pulses of higher groundwater advective fluxes are also hypothesized to have intermittently enhanced flushing of anoxic DIN and biodegraded DOM from porewater and groundwater and suggested dynamic hurricane-induced negative surge events affect net nutrient budgets in estuarine and coastal seas.